Measuring psychological resilience in Internal Security Forces officers - Zubeir Shareef Awla; Sabir Abdullah Saeed Al-Zebary (Zanco Journal of Humanity Sciences)
This research aimed to the following objectives: Measuring the level of psychological resilience in internal security forces in Sulemani province. And Identifying the statistical differences between the levels of psychological resilience in internal security forces in Sulemani province according to some variables such as: sex (male, female), To achieve the objectives of the research, the researcher depended on an Arabic scale developed by Alwan and Talaa (2014), which is consisted of (30) items covering (3) sub-scales as following: psychological re-equilibrium, effective adjustment with stressors that face the person, taking responsibility and facing problems. The items were self-report with five point Likert scale (always, mostly, sometimes, rarely, never) as alternatives for answering. The researcher also conducted the necessary measures to ensure the overall psychometric properties of the scale such as face validity, half-split reliability which was (0.91) and it is considered to be acceptable properties for measuring the variable which is supposed to be measured. When the scale were ready to be applied in their final form, they were applied on a sample of (565) officers in Sulemani province security offices and departments related to ministry of interior. After investigation, it appeared that only (458) questionnaires which were completely answered. Then these answers were checked and total sum was extracted to be processed in statistical analysis to produce research results. Many statistical tools were used, such as: Pearson correlation coefficient, Spearman –Brown formula, one-sample and paired samples t-test, percentage, and mode probability formula by utilizing the statistical package for the social sciences (SPSS). The results according to the objectives were as following: There is psychological resilience in internal security forces of Kurdistan Region-Iraq. The mean score of affective control of the sample was (109.26) which is bigger than the hypothesized mean (90) and the difference between the two means was statistically significant, since the calculated t score was (33.93) which is bigger than the table t (1.96) at (457) degree of freedom and p-value (0.05). And There is statistically significant difference in psychological resilience in officers according to sex variable (male, female), which the average score of males was (92.06) with standard deviation reached (11.38). Meanwhile, the average score of the females was (83.93) with (15.98) standers deviation. The calculated t score was (3.32) which is bigger than the table t (1.98) at (457) degree of freedom and p-value (0.05). Based on the results, some recommendations and suggestion are proposed to the parties related to this research.